2013
DOI: 10.1097/bpo.0b013e3182a00688
|View full text |Cite
|
Sign up to set email alerts
|

Internal Consistency and Validity of the QuickDASH Instrument for Upper Extremity Injuries in Older Children

Abstract: III, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…[22][23][24] Despite these limitations, the study demonstrated good functional and radiographic outcomes for distal displaced humerus metaphyseal fractures in children treated surgically with ESIN.…”
Section: Discussionmentioning
confidence: 86%
“…[22][23][24] Despite these limitations, the study demonstrated good functional and radiographic outcomes for distal displaced humerus metaphyseal fractures in children treated surgically with ESIN.…”
Section: Discussionmentioning
confidence: 86%
“…18 The QuickDASH is a valid instrument for older children and adolescents with upper extremity pathology. 10 The questionnaires used in this study were the next best available for measuring functional outcomes in a pediatric population. The results provide an insight into the effect of corrective osteotomies for distal radius malunions and valuable information for shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The QuickDASH is an eleven item questionnaire designed to measure physical function and symptoms in people with a musculoskeletal disorder of the upper limb, valid for older children and adolescents. 10 The QuickDASH ranges from 0 to 100, with 0 indicating no pain and no functional impairment. 11,12 Surgical Technique All corrective osteotomies were performed by two highly experienced surgeons as classified by Tang.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the Quick-DASH (Quick Disability Arm Shoulder Hand) questionnaire was applied with its optional practicing module (Quick-DASH optional). This instrument was translated and validated for adolescents 20 21 . The range of motion of the internal shoulder rotation was measured using the passive motion technique with a goniometer.…”
Section: Methodsmentioning
confidence: 99%